Treatment of Fecal Incontinence With a Rechargeable Sacral Neuromodulation System: Efficacy, Clinical Outcome, and Ease of Use—Six‐Month Follow‐Up. Issue 7 (27th October 2020) - Jottard, Katleen; Van den Broeck, Sylvie; Komen, Niels; Bruyninx, Luc; De Wachter, Stefan
Abstract: Objective: Sacral neuromodulation is an effective treatment for fecal incontinence (FI) after conservative treatments have failed. A new rechargeable sacral neuromodulation system (r‐SNM) includes a rechargeable implantable neurostimulator (INS). No data is available of the use of this technology in patients with fecal incontinence. Materials and Methods: Fifteen patients with FI were implanted with the Axonics rechargeable SNM system in a single‐stage implant procedure and prospectively followed. Primary outcome was fecal incontinence episodes at four weeks and six months measured with stools diary. Success was defined as at least 50% improvement of fecal incontinence episodes. Additionally, quality of life and ease of use were evaluated. Results: At four weeks, 13 participants (87%) were test responders based on ≥50% reduction in FI episodes as documented on their bowel diary. Weekly FI episodes decreased from a median (25%–75% range) of 8 (5.8–20.3) at baseline to a median of 1.5 (0.4–4.5) at four weeks ( p  = 0.001), and 1.5 (0–2.6) at six months ( p  = 0.001), corresponding to 75% and 79% reduction in weekly FI episodes. Of the 13 subjects having ≥50% reduction in FI episodes at four weeks, 12 (PP = 92%) were therapy responders at six months. There were no unanticipated device or procedure‐related adverse events. Mean time to recharge the system was 37 ± 3 min once or twice per week. All patients were moderately or very satisfied with the system and its effect. Conclusions: The r‐SNM system provides safe and effective therapy in patients with FI at six months.